Implementation of Halal Certification Assistance by LP3H Institut Agama Islam Sahid Bogor for MSMEs in Bogor Regency (2023-2025) - Ermi Suryani; Rully Trihantana; Rifqy Thanthawi (ASEAN Journal of Halal Study, 2025)
Self-declared halal certification is a government-regulated scheme limited to MSMEs products that do not pose a significant risk. There are 1400 products that have been independently certified under the guidance of the LP3H Islamic Institute. The quality and marketing of 90% of certified products require assistance from the Halal Product Guarantee Agency (BPJPH). In launching the government program to assist MSMEs, the Halal Product Certification Service Agency (LP3H) of the Sahid Islamic Institute collaborates with businesses whose products are already halal-certified to enhance the quality and marketing of their products to a broader consumer base. The implementation method of this Community Program begins with, first, collecting data on MSMEs at the Sahid Islamic Institute LP3H. Second, categorizing the types of businesses owned by MSMEs under the LP3H INAIS umbrella. Third, selecting MSMEs based on the suitability of their businesses/products to improve their quality. Fourth, collaborating with MSMEs as partners of the Sahid Islamic Institute LP3H. The objective of the Community Service Program  is to evaluate the quality of MSMEs products and enhance marketing after obtaining free halal certification declared by the Indonesian government. The benefits include improving community welfare and the quality of halal food in Indonesia. The outcomes of this community service are that all MSMEs activities supported are properly documented on an ongoing basis, second is product quality.